2018
DOI: 10.1029/2018jd029000
|View full text |Cite
|
Sign up to set email alerts
|

Future Projections of the Large‐Scale Meteorology Associated with California Heat Waves in CMIP5 Models

Abstract: Previous work showed that climate models capture historical large‐scale meteorological patterns (LSMPs) associated with California Central Valley heat waves including both ways these heat waves form. This work examines what models predict under the Representative Concentration Pathway (RCP) 4.5 and RCP8.5 scenarios. Model performance varies, so a multimodel average weights each model based on its historical performance in four parameters. An LSMP index (LSMPi) defined using upper atmosphere variables captures … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 39 publications
0
11
0
Order By: Relevance
“…It has also been shown that temperature extremes are accompanied by large displacements of air masses that create specific wave patterns-the socalled large-scale meteorological patterns (LSMPs) reviewed in Grotjahn et al (2016)-which are distinct from the climate modes mentioned above. Regional-scale extreme heat in the CCV has been shown to be linked to LSMPs that are an equivalent barotropic, nearly stationary wave train (ridgetrough-ridge) across the North Pacific and western North America (Grotjahn and Faure, 2008;Grotjahn, 2011Grotjahn, , 2013Grotjahn, , 2016Palipane and Grotjahn, 2018). Looking at the general features of LSMPs prior to the onset of heat waves is a good way to connect those heat waves with associated atmospheric phenomena and therefore begin to understand related mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…It has also been shown that temperature extremes are accompanied by large displacements of air masses that create specific wave patterns-the socalled large-scale meteorological patterns (LSMPs) reviewed in Grotjahn et al (2016)-which are distinct from the climate modes mentioned above. Regional-scale extreme heat in the CCV has been shown to be linked to LSMPs that are an equivalent barotropic, nearly stationary wave train (ridgetrough-ridge) across the North Pacific and western North America (Grotjahn and Faure, 2008;Grotjahn, 2011Grotjahn, , 2013Grotjahn, , 2016Palipane and Grotjahn, 2018). Looking at the general features of LSMPs prior to the onset of heat waves is a good way to connect those heat waves with associated atmospheric phenomena and therefore begin to understand related mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…According to Figures 2, 3, and S2 and Tables S2–S5, it can be found that the performance of SCHW in producing the T max from the model ensemble is superior to any single GCM. In previous studies, multiple model ensemble techniques have been broadly used in post‐processing of surface air temperature due to its significant ability in improving the variability of model outputs (Räisänen, 2007; Palipane and Grotjahn, 2018; Yang et al ., 2018; Hu et al ., 2019). Thus, it is crucial to evaluate the ability of the developed SCHW in reproducing the present‐day climate with multiple model ensemble since the outputs will be used to project station‐scale T max and explore the related future extreme high‐temperature events (i.e., heatwaves).…”
Section: Evaluation Of Schwmentioning
confidence: 99%
“…Previously, research efforts have been made in studying the future heatwaves (Xu and Xu, 2012; Cowan et al ., 2014; Xu et al ., 2015; Guo et al ., 2017; Palipane and Grotjahn, 2018). For example, Li et al .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The patterns persist over large spatial and temporal scales, and unlike the high-frequency variations exhibited by surface meteorology, the patterns' spatio-temporal variations are better captured by GCMs. Previous research has sought to link the changes in frequency and return periods of these largescale patterns with the occurrence of extreme events under a changing climate using data from GCMs [26][27][28][29].…”
mentioning
confidence: 99%